2021
DOI: 10.1177/00332941211040441
|View full text |Cite
|
Sign up to set email alerts
|

Does the Fear of Missing Out Moderate the Relationship Between Social Networking Use and Affect? A Daily Diary Study

Abstract: Social networking site (SNS) use is common and speculation about the negative impact of SNS use on mental health and psychological well-being is a recurring theme in scientific debates. The evidence for this link, however, is inconclusive. The Fear of Missing Out (FoMO) may assist in understanding the mixed evidence, as individuals who experience FoMO are more driven to keep up with what is happening to avoid missing out. We used a 2-week daily diary study of 408 university students to measure the daily associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Supporting this, studies have found that people who experience FoMO to a greater extent report more negative affectivity (Elhai et al, 2018, 2020b). However, evidence for the relationship between FoMO and positive affect has been more limited and inconclusive (Li et al, 2020; Milyavskaya et al, 2018; Riordan et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Supporting this, studies have found that people who experience FoMO to a greater extent report more negative affectivity (Elhai et al, 2018, 2020b). However, evidence for the relationship between FoMO and positive affect has been more limited and inconclusive (Li et al, 2020; Milyavskaya et al, 2018; Riordan et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can be further speculated that for those young individuals with high FoMO, who satisfy their needs of relatedness by messaging, posting, and browsing on social media might increase affective-well-being and reduce loneliness. Preliminary evidence among young adults suggests that FoMO moderated the relationship between social media use and negative affect (Riordan et al, 2021). Moreover, among adolescents (aged 11–19) with high levels of FoMO, general social media use was positively related to subjective well-being (Chai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%